Pengaruh Volume Transaksi Saham, Indeks Dow Jones dan Uang Beredar Terhadap Indeks Harga Saham Gabungan (IHSG) Bursa Efek Indonesia (BEI) Tahun 2018-2020 - Duta Andriansyah; Fazhar Sumantri; Chaerina Chaerina; Alfia Dwi Damayanti; Refo Putra Pangestu; Intan Septiani; Siti Livka Hadinia Soliha (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the volume of stock transactions, the Dow Jones index, and the money supply related to the Composite Stock Price Index (CSPI) of the Indonesia Stock Exchange (IDX) in 2018-2020. Multiple regression analysis method was used in research analysis using IBM SPSS Statistics 25. The data collection method used documentation. Simultaneous test results (Test F) are seen from Stock Transaction Volume (X1), Money Supply (X2), Dow Jones Index (X3), for the period 2018-2020, the Composite Stock Price Index (JCI) will have a significant impact. The results of the partial test analysis (t test) can be concluded that overall the X variable has a positive and significant influence on the Composite Stock Price Index (Y). The coefficient of determination of 0.798 is the same as 79.8 percent of the three independent variables simultaneously.